Implementation of Murabahah Contract in Islamic Financial Institutions: A Theoretical and Practical Review - Abdillah Mahdi; Purwanto; Siti Hidayati; Intan Wulandari; Muhamad Ibnu Malik (Konsultan Jurnal Ilmiah Indonesia, 2025)
The murabahah contract is one of the most widely used sale and purchase contracts in the operations of Islamic financial institutions, particularly in financing products. The implementation of this contract is based on the principle of price transparency and agreed profit margins between the Islamic financial institution and the customer. However, in practice, the implementation of the murabahah contract often gives rise to differences in understanding and potential deviations from ideal sharia principles. This article aims to analyze the implementation of the murabahah contract in Islamic financial institutions through theoretical and practical reviews. The research method used is a literature review by examining various sources of literature in the form of textbooks, scientific journals, fatwas from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and regulations related to the murabahah contract. The results of the study indicate that theoretically the murabahah contract has a strong sharia basis and clear mechanisms, but in practice there is still a tendency for its implementation to resemble conventional financing systems, particularly in aspects of goods ownership and profit margin determination.